Study of comparative aspects of gastroretentive delivery of cefixime trihydrate from microspheres and microsphere based tablets - Mishra B.; Singh A.K.; Yadav S.K. (My University, 2025)
The research was performed to develop and evaluate floating gastroretentive microsphere based tablets of cefixime trihydrate (CFT) which shows poor oral bioavailability (40–50 %) due to narrow absorption window. The microspheres were prepared by varying ratios of hydroxypropylmethyl cellulose (HPMC) and ethyl cellulose using non-aqueous solvent evaporation method. Fourier transform infrared analysis of prepared microspheres demonstrated the compatibility of drug and polymers. Differential scanning calorimetric and X-ray diffraction studies confirmed changes in crystalline structure of CFT within the formulation. Scanning electron microscopy showed spherical and porous nature of microspheres. Microspheres were characterized for particle sizes (70–160 µm), percentage yield (84–95 %), and encapsulation efficiencies (35–80 %). Micrometric parameters such as angle of repose, Carr’s index were in acceptable limit and indicated microsphere elicited free flowing behaviour. Tableted microspheres illustrated buoyancy for more than 12 h as compared to drug tablets. In vitro release of drug was more controlled and prolonged on tableting the microspheres exhibiting biphasic pattern. Kinetically, microspheres followed Fickian (case I) diffusion mechanism while tableted microspheres followed non-Fickian diffusion (anomalous) mechanism for CFT release. Conclusively, tableting of microsphere into swellable and controlled release polymers like HPMC are expected to enhance gastric retention and bioavailability of CFT due to small particle size, changes in crystallinity of CFT, prolonged floating behavior and controlled release profile. © 2015, The Korean Society of Pharmaceutical Sciences and Technology.